DAKWAH PADA MASYARAKAT TERASING Studi Analisis tentang Tipologi Mitra Dakwah â€œSuku Anak Dalamâ€ di Taman Nasional Bukit Dua Belas Jambi - Wisri Wisri (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2014)
Tribal Child Within is part of a group of indigenous people who were in the Jambi region spread over three districts namely Batang Hari, Bungo and Tebo Sarolangun Bangko and which is the object of this study is the tribe who live at Children In Park Hill twelve Black Water District Sarolangun Jambi. They are his remote, isolated, left behind in the economic, educational, health, social, political and religious. To meet the needs of daily life conducted by collecting forest products and hunting animals.Focus of this study is to describe the characteristics or typology Tribal Children In terms of cultural, socialÂ  and economic. With the aim of understanding the characteristics of the tribe after the Child Within, the authors could find an effective strategy for the propagation of the Tribal Children In and other isolated communities which have such characteristics Spare the Child Within. To answer the above problems is first author of observation and interviews to several parties involved in this study and analyzed (Content analisys). From these data and translate it into the category of the author and pass into units , then draw conclusions inductively to construct an effective theory in preaching on Tribal Child Within.From this study, the authors that an effective strategy for the propagation of the Tribal Children In preaching the approach is the cultural, economic approach, social approach and the final approach to language as propaganda entrance on Children In Tribal communities.